2018
DOI: 10.2147/cia.s150067
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and psychological consequences in elderly patients after a hip fracture: a review

Abstract: Fractures due to fragility of the bone around the hip joint have become a major public health issue, presenting with an increasing incidence due to the growth of the elderly population. The purpose of this review was to evaluate the impact of hip fractures on the quality of life (QoL), health status (HS), functioning, and psychological parameters, and factors influencing the outcome and the appropriate interventions for improvement of elderly patients. A systematic electronic search of the relevant literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
193
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(215 citation statements)
references
References 70 publications
8
193
0
14
Order By: Relevance
“…The quality assessment is based on three different sub-scales presented by Hagströmer et al: internal validity (IV)-addresses methodological bias, external validity (EV)-addresses the extent that the findings can be generalized to the population based on the study subjects, and quality of the reported data (QV)-assesses if the information provided is sufficient and unbiased [17]. The quality assessment checklist used in this review is based on the 15-item checklist proposed by Ghislieri et al, which is similar to those commonly used in the literature for systematic reviews [17][18][19][20][21]. The score, or number of "Yes"s, was calculated for each article.…”
Section: Introductionmentioning
confidence: 99%
“…The quality assessment is based on three different sub-scales presented by Hagströmer et al: internal validity (IV)-addresses methodological bias, external validity (EV)-addresses the extent that the findings can be generalized to the population based on the study subjects, and quality of the reported data (QV)-assesses if the information provided is sufficient and unbiased [17]. The quality assessment checklist used in this review is based on the 15-item checklist proposed by Ghislieri et al, which is similar to those commonly used in the literature for systematic reviews [17][18][19][20][21]. The score, or number of "Yes"s, was calculated for each article.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in quality of life in contemporary medicine is also a form of response to challenges and demands it faces, which result from increasing occurrence of chronic and progressing diseases in societies. It is also related to increasing life expectancy, thus the period in which patients's functioning is substantially disturbed is extended, which in uences the patient's life situation and its subjective reception [5,14].…”
Section: Discussionmentioning
confidence: 99%
“…It is a preventable and treatable mental health disorder characterized by sadness, hopelessness, irritability, guilt, fatigue, changes in appetite, and contemplation of death or suicide for at least 2 weeks (The National Institute of Mental Health, ). Depression is a significant risk factor for disability and chronic pain in patients with LBP (Parreira et al, ; Pinheiro et al, ), neck pain (Nazari, Bobos, Billis, & MacDermid, ), knee pain (Phyomaung et al, ), traumatic injury (Alexiou, Roushias, Varitimidis, & Malizos, ; Archer et al, ), and postoperative patients (Wahlman et al, ; Wilson et al, ). Screening for and proactively treating depression can significantly influence an individual's outcome and quality of life (Breland, Mignogna, Kiefer, & Marsh, ; The National Institute of Mental Health, ; Thota et al, ).…”
Section: Multidimensional Psychosocial Screening Toolsmentioning
confidence: 99%